Continuing clozapine with granulocyte colony-stimulating factor in patients with neutropenia. (October 2013) - Khan, Al Aditya; Harvey, Jake; Sengupta, Samrat
Background: The current guidelines dictate that clozapine should be stopped following the emergence of neutropenia. Various alternative approaches have been tried in the past, among them one rarely used alternative being to continue treatment with clozapine with coprescription of granulocyte colony-stimulating factor (G-CSF). Aim and method: In this case series we aim to describe the treatment and progress of a number of patients in a secure psychiatric hospital in the UK. These patients were restarted on clozapine in combination with G-CSF, in spite of previous neutropenia associated with clozapine treatment. Discussion and conclusion: We hope that this case series will raise the profile of a potentially effective alternative to discontinuing clozapine after neutropenia.